Kebijakan Publik dan Reformasi Administrasi : Studi Kasus Pada Kabupaten Jembrana Bali - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Esa Wahyu Endarti (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
Administrative reform led to the concept of reinventing government and has been adapted in Indonesia. The transformation of bureaucracy is not easy, especially the bureaucracy in Indonesia are already getting a bad image in society. Renewal of the government bureaucracy-based entrepreneurship is done to improve the performance and efficiency, create new innovations are creative, and become bureaucracies more responsive and accountable. The concept has been developed and implemented one of the local government district of Jembrana. Head of the Regency of Jembrana has been able to fix one by one arrangement of the bureaucracy. First, the restructuring of government organizations become leaner intended to obtain an effective and efficient organization. Second, every program and activities undertaken in the district of Jembrana coupled with a clear regional regulation that is able to accommodate the interests of local communities. Third, the ability and commitment to achieve the objectives of the Regional Head of development by providing good public service to the society with its priorities. Jembrana was one area that can be role models for innovation programs that better governance (good governance). Reform of the administration (bureaucracy) in response to government demands for the establishment of an efficient government apparatus, effective, responsible, clean and free of corruption.